Comorbid conditions as predictors of mortality in severe COPD – an eight-year follow-up cohort study - Gabriella Eliason; Christer Janson; Gunnar Johansson; Kjell Larsson; Anders Lindén; Claes-Göran Löfdahl; Thomas Sandström; Josefin Sundh (European Clinical Respiratory Journal, 2023)
ABSTRACTPurpose Co-morbidities are common in chronic obstructive pulmonary disease (COPD) and are associated with increased morbidity and mortality. The aim of the present study was to explore the prevalence of several comorbid conditions in severe COPD, and to investigate and compare their associations with long-term mortality.Methods In May 2011 to March 2012, 241 patients with COPD stage 3 or 4 were included in the study. Information was collected on sex, age, smoking history, weight and height, current pharmacological treatment, number of exacerbations the recent year and comorbid conditions. At December 31st, 2019, mortality data (all-cause and cause specific) were collected from the National Cause of Death Register. Data were analyzed using Cox-regression analysis with gender, age, previously established predictors of mortality and comorbid conditions as independent variables, and all-cause mortality and cardiac and respiratory mortality, respectively, as dependent variables.Results Out of 241 patients, 155 (64%) were deceased at the end of the study period; 103 patients (66%) died of respiratory disease and 25 (16%) of cardiovascular disease. Impaired kidney function was the only comorbid condition independently associated with increased all-cause mortality (HR (95% CI) 3.41 (1.47-7.93) p=0.004) and respiratory mortality (HR (95%CI) 4.63 (1.61 to 13.4), p = 0.005). In addition, age ≥70, BMI <22 and lower FEV1 expressed as %predicted were significantly associated with increased all-cause and respiratory mortality.Conclusion In addition to the risk factors high age, low BMI and poor lung function; impaired kidney function appears to be an important risk factor for mortality in the long term, which should be taken into account in the medical care of patients with severe COPD.